Implementation of management accounting in the Portuguese public administration and perception of its purpose - Liberato, M. I.; Paiva, I. C. de S.; Serrasqueiro, R. (Accounting and Management Review, 2025)
This study seeks to examine how financial officers within the Portuguese central public administration perceive the impact of implementing management accounting reform on control, transparency, and management reporting. The research methodology is based on a questionnaire sent to all central public administration organizations in Portugal and the data were analysed using a structural equation model by the Partial Least Square tool. Our results show the perception of financial officers about the implementation of management accounting has a very significant positive effect on increasing the quality of management reports, transparency, and control of public administrations. Thus, it can be concluded that public sector financial officers perceive that the intended objectives of the accounting reform are being successfully achieved. This is a unique opportunity to study the implementation of the management accounting reform, allowing us to know the perceptions of those financial officers about the impact that the implementation of management accounting has on management control, transparency, and reporting. Our study focused only on the central government in Portugal, with a response rate of 34%, requiring also an extended analysis in the setting of local and regional governments, once both were also targets of this reform. This study aids public institutions in understanding the advantages of implementing management accounting; this includes aspects such as control, enhancing organizational efficiency and effectiveness, improving transparency in public spending, and elevating the quality of reporting. This study contributes to shedding light on the role of management accounting in making decisions more aligned with the needs of society.